S125 A comprehensive multi-disciplinary approach to percutaneous endoscopic gastrostomy insertion for complex patients with chronic respiratory failure. (December 2018) - Reddy, A; Anderson, S; Arrandale, L; Dunn, J; Marino, P; Murphy, PB; Ramsay, M; Steier, J; Suh, ES; Thomas, H; Hart, N; Kaltsakas, G
Abstract : Percutaneous endoscopic gastrostomy (PEG) is reported as the favoured approach in patients without chronic respiratory failure with radiologically inserted gastrostomy insertion reserved for patients with severe respiratory compromise. 1 The aim of this study was to evaluate the outcome for patients with chronic respiratory failure receiving PEG insertion as part of a multidisciplinary team approach in a respiratory intensive care unit setting. A retrospective observational study was conducted with all patients admitted for PEG insertion between September 2014 and April 2018. PEG were inserted with procedural intravenous anaesthesia and analgesia (Propofol infusion and Fentanyl boluses, and local anaesthesia to skin with Lidocaine 1%) using invasive, via a tracheostomy, or non-invasive mechanical ventilation on pressure control mode. An established gastrostomy insertion team, including a) gastroenterologist consultant, senior assistant and two senior nurses/practitioners; b) respiratory consultant and senior nurse; and c) anaesthetic consultant and operating departmental practitioner, performed all the procedures. 129/132 (98%) of the PEG procedures were performed successfully. There were 79 males with age 52±19 years. Six (5%) were quaternary referrals following failed PEG insertion and 25 (19%) were for PEG replacements (table 1). Length of stay for motor neurone disease (MND) (3 days; 2, 4 days) was lower compared to the other diagnoses (6 days; 3, 73 days; p<0.001). Survival from PEG insertion was 652±74 days for Duchenne muscular dystrophy (DMD), 369±38 days for MND and 661±50 days for the other diagnoses. MND survival time was lower than DMD (p=0.017) and other diagnoses (p=0.008). Thirty-day mortality was 6.9% and 90 day mortality was 9.9%. All patients that died in the first 90 days had a diagnosis of MND. PEG insertion in complex neuromuscular patients in a respiratory intensive care setting is safe and effective. However, MND survival post PEG insertion is lower than other diagnostic groups. PEG insertion in MND patients should be carefully considered. Reference: Stavroulakis T, Walsh T, Shaw PJ, McDermott CJ. Gastrostomy use in motor neurone disease (MND): A review, meta-analysis and survey of current practice. Amyotrophic Lateral Scler Frontotemporal Degener 2013;14:96–104.